2014
DOI: 10.1177/0956462414544722
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of suicidal ideation and associated factors among HIV-positive MSM in Anhui, China

Abstract: The aim of this study was to investigate the prevalence and factors associated with suicidal ideation among HIV-positive men who have sex with men (MSM) in Anhui, China. A cross-sectional study was conducted to recruit HIV-positive MSM in Anhui, China. A total of 184 HIV-positive MSM gave informed consent and completed the interview. Correlates of suicidal ideation were assessed using multivariable logistic regression. Fifty-seven (31%) of HIV-positive MSM had suicidal ideations within six months before the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 35 publications
8
61
1
Order By: Relevance
“…Findings of high proportions of suicidal ideation (29.7%) and suicidal attempt (9.0%) among PLWH in the current study were similar to those of an earlier study of 184 HIV-seropositive MSM in Anhui province of China (suicidal ideation 31.0% and suicidal attempt 5.4%) [24]. Though the two studies had similar proportions of suicidal ideation, the Anhui study collected information on suicide 6 months prior to the study, whereas the present study collected suicidal information since HIV-seropositive diagnosis and the median duration since HIV diagnosis was 2.7 years.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Findings of high proportions of suicidal ideation (29.7%) and suicidal attempt (9.0%) among PLWH in the current study were similar to those of an earlier study of 184 HIV-seropositive MSM in Anhui province of China (suicidal ideation 31.0% and suicidal attempt 5.4%) [24]. Though the two studies had similar proportions of suicidal ideation, the Anhui study collected information on suicide 6 months prior to the study, whereas the present study collected suicidal information since HIV-seropositive diagnosis and the median duration since HIV diagnosis was 2.7 years.…”
Section: Discussionsupporting
confidence: 90%
“…Among the PLWH who were homosexual/bisexual, two-thirds (66.4%) were never married. PLWH who were homosexual/bisexual were facing double stigma from both HIV infection and sexual orientation [24, 4547]. In the traditional Chinese culture, getting married, bearing children, and carrying on family names are considered to be the most important responsibilities for men [45, 47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are an estimated 17.8 million MSM in China, and some studies showed that Chinese MSM experienced high levels of gay‐related prejudice or stigma (Feng, Wu, & Detels, ; Li, et al, ; Liu & Choi, ) and significantly elevated prevalence of psychiatric disorders (Yu et al, ), emotional symptoms (Huang et al, ; Zhang, et al, ), and suicidal behaviors (Wu et al, ; Wang et al, ; Yu, ; Zhang et al, ; Zheng, Wang, Wu, Zhang, & Pi, ; Zhang, Wang, Zheng, Xu, & Wang, ). Despite the growing interest in identification of the risk factors for suicidality in the Chinese population of MSM, few studies have systematically assessed the risk factors for suicidal behaviors by use of international standardized questionnaires and instruments.…”
Section: Introductionmentioning
confidence: 99%